THE CORRELATIONS OF EFL STUDENTS' SELF-EFFICACY & PUBLIC SPEAKING ABILITY - Mutia Aisyah (Integrative Perspectives of Social and Science Journal, 2025)
This study aims to determine is there correlation between students’ self-efficacy level and their public speaking ability. This type of research is a quantitative correlational study using a descriptive method. The population consists of all 10th-grade students in the 2024/2025 academic year at MAN Kota 3 Palangka Raya. The sample was selected using simple random sampling with the Slovin formula, resulting in 77 students. Data were obtained through a self-efficacy questionnaire and a public speaking test. The data analyz using a correlation test. The results show that the students' self-efficacy moderate category, while their public speaking ability is at a poor level. There is a positive and significant correlation between self-efficacy and public speaking ability, with a correlation coefficient of r =0.755, p < 0.05. These findings imply that enhancing students' self-efficacy positive impact their public speaking. Therefore, educators are encouraged to create learning environments confidence and motivation.